2012
DOI: 10.1007/s00216-012-6381-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensors and biosensors based on polyelectrolyte microcapsules containing fluorescent dyes and enzymes

Abstract: The concept of enzyme-assisted substrate sensing based on use of fluorescent markers to detect the products of enzymatic reaction has been investigated by fabrication of micron-scale polyelectrolyte capsules containing enzymes and dyes in one entity. Microcapsules approximately 5 μm in size entrap glucose oxidase or lactate oxidase, with peroxidase, together with the corresponding markers Tris(4,7-diphenyl-1,10-phenanthroline)ruthenium(II) dichloride (Ru(dpp)) complex and dihydrorhodamine 123 (DHR123), which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…Polyelectrolyte multilayers (PEMs) formed by the layer-by-layer technique [1,2] have attracted considerable interest because of their potential applications in optical devices [3][4][5], sensing [6][7][8], drug release [9,10], and biologically active coatings [11][12][13][14][15]. The PEM film is based on the alternating adsorption of oppositely charged polyions onto a charged surface.…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolyte multilayers (PEMs) formed by the layer-by-layer technique [1,2] have attracted considerable interest because of their potential applications in optical devices [3][4][5], sensing [6][7][8], drug release [9,10], and biologically active coatings [11][12][13][14][15]. The PEM film is based on the alternating adsorption of oppositely charged polyions onto a charged surface.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing pH in cells [106] or oxygen [107] is relevant for sensoring part of theranostics [97]. This can be implemented by designing a semipermeable capsule which would permit ions to go through its shell [108], but would protect and preserve inside the larger molecules (proteins), which are used as indicators or sensors.…”
Section: Multiple Stimuli Release and Multicompartment Structures-relmentioning
confidence: 99%
“…It is widely used in the creation of biosensors [11,12] or the polyelectrolyte titration [13]. Moreover, Baumgartner et al [14] reported the decreasing in the indices of the apparent ionization constant of neutral red, app a pK , by 1.7 units in NaPSS solution on adding aprotic solvent dioxane (2.0 M).…”
Section: Introductionmentioning
confidence: 99%